Analysing the conceptual framework of religious freedom and interreligious relationship in Islam - Mohd Roslan Mohd Nor; Issa Khan; Mohammad Elius (Indonesian Journal of Islam and Muslim Societies, 2018)
This study evaluates the concept of religious freedom and interreligious relationships in Islam. The research engages in textual analysis and historical interpretation of the Qur’an and Sunnah (the Prophetic tradition) regarding the freedom of religious beliefs and practices as well as Muslim relationships with people of other religions. The study shows that Islam plays a unique role in providing every individual with the complete freedom to possess and practiceany religion, culture or ideology. It also shows that as a universal religion,Islam advocates a harmonious relationship among the people of differentreligions, cultures and civilisations for the peaceful coexistence and harmoniousdevelopment of all human beings. The study concludes that Islam as a completeway of life preserves the beliefs and practices of every individual and maintainsa peaceful relationship between the followers of one religion and another. Itconstitutes a viable model for resolving religious hatred and promoting peaceand justice among people of diverse ethnic, religious and cultural backgrounds.